Answer to Question #248532 in Differential Equations for Jick

Question #248532
(2x+3)dy/dx -y+(2x+3)
1
Expert's answer
2021-10-11T16:29:40-0400

"(2x+3)\\frac{dy}{dx}-y=0\\\\\n\\Rightarrow \\frac{dy}{dx}=\\frac{y}{2x+3}\\\\\n\\Rightarrow \\frac{dy}{y}=\\frac{dx}{2x+3}"

Integrating both sides, we get:

"ln(y)=\\frac{ln(2x+3)}{2}+ln(c)\\\\\n\\Rightarrow 2ln(y)=ln(2x+3)+2ln(c)\\\\\n\\Rightarrow ln(y^2)=ln(2x+3)+ln(c^2)\\\\\n\\Rightarrow ln(y^2)=ln(c^2(2x+3))\\\\\n\\therefore y^2=c^2(2x+3)\\\\\n\\Rightarrow y^2=C(2x+3)"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog